Importance of Trust Towards University Students: A Determinant of Online Shopping Behavior - Jin, Lim Yi; Azuddin, Bahari; Abdullah, Osman; Hanum, Hassan; Abdul Rahim, Romle; Sin, Kit Yeng; Ling, Sim Choon (American Scientific Publishers, 2016)
E-commerce has been extensively promoted by Malaysian government in this technology era. This research was conducted in tandem with government effort to promote internet shopping while to explore the level of trust and its influence on internet shopping among the undergraduate and postgraduate students in one higher learning institution of Malaysia. A quantitative survey approach was applied throughout the study and finally, a total 662 out of 800 questionnaires were applicable for data analysis using SPSS and AMOS. Multi-stage sampling method by combined stratified and systematic sampling was utilized in this study. The results indicated the overall score for trust was of moderate level and the positive and significant relationship between trust and online shopping behavior has been identified. Subsequently, future research was proposed to enclose other relevant instruments that suit to Malaysian context and working adults that consisted of 18 to 34 years old. This paper provide informative outlines to the retailers especially for those who were currently operating or planning to embrace online business particularly regards to the significance of trust to the customers in the virtual environment. Malaysia itself could benefit from this research to enforce the internet security that serve internet a safe and secure platform to perform transaction.